A Comprehensive Review on the Synthesis and Energy Applications of Nano-structured Metal Nitrides - Ashraf, Iffat; Rizwan, Syed; Iqbal, Mudassir (Frontiers in Materials, 2020)
Nanosized metal nitrides, due to their chemical characteristics which make them sustainable alternatives to noble metals in catalysis, have drawn the attention of researchers worldwide. Transition metal nitrides are very similar in their method of synthesis, properties, and applications. Their synthetic parameters are considered to be the main factor for determining the effectiveness of metal nitrides in photocatalysis, energy storage devices, remediation of environmental pollutants, gas sensors, and biomedical applications. This review focuses on very recent advances made in synthetic approaches and electrocatalytic applications of metal nitrides. The synthetic approaches will provide an overview of cost of production and consumption of energy and time required for synthesis. Furthermore, some recent techniques that offer new paths for researchers, such as electrochemical, sol-gel, solvothermal, sonochemical, solid-state reaction, chemical synthesis, and many more, are also discussed. Various applications in electrocatalysis, water splitting, lithium ion batteries, and super-capacitors, etc. are summarized. We are confident that this review will provide very useful information for the upcoming community of researchers interested in synthesizing nitrides for various applications.